2021
DOI: 10.1186/s12958-021-00733-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐actinin‐4 is essential for maintaining normal trophoblast proliferation and differentiation during early pregnancy

Abstract: Background Proper differentiation of trophoblasts in the human placenta is essential for a successful pregnancy, whereas abnormal regulation of this process may lead to adverse pregnancy outcomes, especially preeclampsia (PE). However, the underlying mechanism of trophoblast differentiation remains unclear. Previous studies have reported the involvement of alpha-actinin-4 (ACTN4) in the actin cytoskeleton dynamics and motility. Hence, we hypothesized that ACTN4 may act as an important regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In addition, the differentiation of CTB is also related to changes in cytoskeletal organization and adhesion structures, indicating that cytoskeletal integrity and appropriate remodelling may affect trophoblast cell invasion 54 . ACTN4, an actin binding protein, is mainly expressed in placental CTB cells and participated in actin cytoskeleton dynamics and motility 54,55 . Previous evidence suggested that ACTN4 dysregulation may lead to compromised invasiveness in trophoblasts and abnormal cytoskeletal remodelling by inhibiting AKT phosphorylation, which may ultimately contribute to PE 54,55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the differentiation of CTB is also related to changes in cytoskeletal organization and adhesion structures, indicating that cytoskeletal integrity and appropriate remodelling may affect trophoblast cell invasion 54 . ACTN4, an actin binding protein, is mainly expressed in placental CTB cells and participated in actin cytoskeleton dynamics and motility 54,55 . Previous evidence suggested that ACTN4 dysregulation may lead to compromised invasiveness in trophoblasts and abnormal cytoskeletal remodelling by inhibiting AKT phosphorylation, which may ultimately contribute to PE 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“… 54 ACTN4, an actin binding protein, is mainly expressed in placental CTB cells and participated in actin cytoskeleton dynamics and motility. 54 , 55 Previous evidence suggested that ACTN4 dysregulation may lead to compromised invasiveness in trophoblasts and abnormal cytoskeletal remodelling by inhibiting AKT phosphorylation, which may ultimately contribute to PE. 54 , 55 Filamins (FLNs) as scaffolds for signalling proteins and adhesive receptors that regulate actin cytoskeleton remodelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O-GlcNAc regulation of translation 27 and the actin cytoskeleton 28 are of undoubted interest in relation to placental function. Reduced translation, as a consequence of increased eIF2α phosphorylation, reportedly contributes to placental dysfunction in pregnancies complicated by fetal growth restricted 29 , trophoblast turnover, fusion and motility are all influenced by cytoskeletal dynamics 30 33 , as is integrity of the endothelial barrier 34 . However, here we chose clathrin-mediated endocytosis (CME) for further study.…”
Section: Discussionmentioning
confidence: 99%
“…The ACTN4 gene encodes for an actin-binding protein with multiple roles in different cell types, and is well known for causing focal segmental glomerulosclerosis [71][72][73] . The gene product is also involved in the maintenance of cytoskeletal structure, modulating cell motility and regulating endothelial cells 74,75 , and may play a role in placentation 76 . ACTN4 has been suspected to act as a regulator of trophoblast proliferation and differentiation during early pregnancy, and has been shown to have reduced expression in severe preeclampsia 76 .…”
Section: Pe-htpmentioning
confidence: 99%